Sufi Muslims in Montréal: Tensions between Cosmopolitanism and the Cultural Economy of Difference - LeBlanc, Marie Nathalie (Anthropologica, 2013)
In this article, I describe how expressions of West ern modernity—secularism, tolerance and cosmopolitanism— are articulated in post-9/11 Quebec. I explore the socio-political relevance of the appeal to cosmopolitanism in a neoliberal post-Cold War context where modern ideals of secularism have been deeply unsettled and the idea of post-secularism is taking hold. I consider how some Muslims, members of a Sufi circle, initiate forms of civic participation that position Islam as a site for intercultural negotiation and for the articulation of cosmopolitan religious identities. A discourse on spirituality brings together Sufi mysticism and a local Québécois version of openness to sociocultural diversity.